The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1042/bj1620099
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of benzyl isothiocyanate and its cysteine conjugate

Abstract: 1. The corresponding cysteine conjugate was formed when the GSH (reduced glutathione) or cysteinylglycine conjugates of benzyl isothiocyanate were incubated with rat liver or kidney homogenates. When the cysteine conjugate of benzyl isothiocyanate was similarly incubated in the presence of acetyl-CoA, the corresponding N-acetylcysteine conjugate (mercapturic acid) was formed. 2. The non-enzymic reaction of GSH with benzyl isothiocyanate was rapid and was catalysed by rat liver cytosol. 3. The mercapturic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(109 citation statements)
references
References 26 publications
2
105
1
Order By: Relevance
“…A whole body autoradiographic study in rats suggested that apart from the gastrointestinal tract, liver and kidneys, only the blood contained relatively higher concentrations of ITC metabolites (Franklin, E. R., unpublished, cited in [177]). Following application of 14 C labelled ITCs to rats, high concentrations of 14 C appeared rapidly in stomach, small intestine, ceacum, and colon, intermediate concentrations in pancreas and spleen, and very low concentrations in heart and brain.…”
Section: Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…A whole body autoradiographic study in rats suggested that apart from the gastrointestinal tract, liver and kidneys, only the blood contained relatively higher concentrations of ITC metabolites (Franklin, E. R., unpublished, cited in [177]). Following application of 14 C labelled ITCs to rats, high concentrations of 14 C appeared rapidly in stomach, small intestine, ceacum, and colon, intermediate concentrations in pancreas and spleen, and very low concentrations in heart and brain.…”
Section: Distributionmentioning
confidence: 99%
“…It contains high concentrations of GSH and shows the highest GST activity in the organism. As described for small intestinal ITC metabolism, enzymatic and nonenzymatic conjugation with GSH is the major route of metabolism [177,198]. At high concentration of ITCs this may lead to a temporary GSH depletion and an increased binding to cellular macromolecules [187].…”
Section: Metabolism and Excretionmentioning
confidence: 99%
“…Following their absorption into the intestinal epithelium isothiocyanates are released into the systemic circulation and metabolized by the mercapturic acid (MA) pathway in the liver. Isothiocyanates initially form conjugates with glutathione, then undergo enzymic modification and are excreted in urine as their corresponding N-acetylcysteine conjugates or MA (Brüsewitz et al 1977;Mennicke et al 1983). Urinary isothiocyanate MA excretion therefore partially reflects isothiocyanate absorption in vivo, although variation in pre-and postabsorptive recovery may also be important.…”
Section: Digestive and Post-absorptive Fate Of Glucosinolates After Imentioning
confidence: 99%
“…An understanding of the digestive and absorptive fate of dietary glucosinolates and their isothiocyanate metabolites has emerged mostly from mechanistic studies in animal models such as rats and hamsters (Brüsewitz et al 1977;Mennicke et al 1983;Michaelsen et al 1994;Duncan et al 1997;Elfoul et al 2001). The low recoveries of intact glucosinolates and their metabolites in faeces of animals fed glucosinolates or isothiocyanates suggest that a substantial proportion of ingested glucosinolates and isothiocyanates are metabolised in vivo (Slominski et al 1988;Bollard et al 1997;Rouzaud et al 2003).…”
Section: Digestive and Post-absorptive Fate Of Glucosinolates After Imentioning
confidence: 99%
“…Isothiocyanates ITCs (R-N=C=S) are electrophilic compounds and are known to react predominantly with thiols, and to a much lesser extent with NH2 and OH groups (Drobinica et al, 1965;Brusewitz et al, 1977). Therefore, the major route of metabolism and elimination of ITCs from the body is the mercapturic acid pathway i.e.…”
Section: Discussionmentioning
confidence: 99%